2019
DOI: 10.1021/acssensors.9b00039
|View full text |Cite
|
Sign up to set email alerts
|

SERS-Based Pump-Free Microfluidic Chip for Highly Sensitive Immunoassay of Prostate-Specific Antigen Biomarkers

Abstract: Highly sensitive analysis of cancer biomarkers demonstrates an important impact in early diagnosis and therapies of cancer. A novel surface-enhanced Raman scattering (SERS) based immunoassay using microfluidic technique was reported for rapid analysis of prostatespecific antigen (PSA) biomarker. It is a useful screening test to discriminate prostate cancer and other diseases related to prostate. A "sandwich" immunoassay based on SERS nanotags, PSA biomarkers, and magnetic beads was applied on a pump-free micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 32 publications
0
58
0
Order By: Relevance
“… 23 For instance, the combination of SERS with microfluidic devices has been applied to rapid analysis of food contaminants, 24 multiplex recognition of interleukins from blood plasma, 25 and detection of prostate cancer biomarkers. 26 Aberasturi et al focused on using microfluidic devices and 3D SERS imaging to distinguish unlabeled and nanotag-labeled fibroblast cells to mimic different cell populations within a tissue. 27 Moreover, Altunbek et al used SERS and the hanging drop method to monitor the cellular response to drug exposure.…”
mentioning
confidence: 99%
“… 23 For instance, the combination of SERS with microfluidic devices has been applied to rapid analysis of food contaminants, 24 multiplex recognition of interleukins from blood plasma, 25 and detection of prostate cancer biomarkers. 26 Aberasturi et al focused on using microfluidic devices and 3D SERS imaging to distinguish unlabeled and nanotag-labeled fibroblast cells to mimic different cell populations within a tissue. 27 Moreover, Altunbek et al used SERS and the hanging drop method to monitor the cellular response to drug exposure.…”
mentioning
confidence: 99%
“…Specific integrated biochips have been designed for the entire sample-to-targeted gene analysis of prostate cancer in urine and serum samples [ 177 ]. Gao et al reported an immunoassay sensor based on surface-enhanced Raman scattering (SERS) with microfluidic technique to quickly detect PSA [ 182 ]. The immunoassay platform “sandwich,” consisting of SERS nano-tags, magnetic beads and PSA biomarkers, on a pump-free microfluidic biosensor ( Figure 11 ).…”
Section: Nanomaterials Towards Diagnosis and Biosensing Of Prostatmentioning
confidence: 99%
“…Using this chip, the PSA detection limit is estimated to be below 0.01 ng/mL. This PSA biomarker detection level in human serum can be achieved in 5 min without manual incubation or hard dialysis machine [ 182 ]. In another study, Feng et al documented an integrated PSA immunodetection microfluidic chip using a giant magnetoimpedance (GMI) sensor with a detection limit as small as 0.1 ng/mL and operates in the concentration range of 0.1–20 ng/mL [ 183 ].…”
Section: Nanomaterials Towards Diagnosis and Biosensing Of Prostatmentioning
confidence: 99%
“…With a myriad number of patient fluid samples, they use chemical reactions between an antibody to its antigen [75] to quantify substances such as glucose, cholesterol, proteins and enzymes in patient fluid samples. Automated systems range in size from smaller systems that hold a limited number of reagent samples (<100) [76] and run a limited number of tests to larger systems that hold a large number of reagent samples (>500) and run a wide range of tests. Required reagents are often stored onboard the system, and held at a constant temperature, typically between 4 • C to 8 • C [77].…”
Section: Immunoassaymentioning
confidence: 99%